Issues of insuring financial risks of leasing in project financing - А. V. Serinova; T. Yu. Shemyakina (Вестник университета)
The issue of leasing financial risks insurance in project financing has been considered, which consists in the lack of wide spread of this type of insurance in the Russian market. The purpose of the study is to propose recommendations for credit organizations to reduce the impact on the leasing process, which would contribute to a wider spread of financial risk insurance. Within the framework of using the system, comparative, and logical analysis methods it has been established that today leasing is one of the most promising types of attracting financing, as well as one of the tools of project financing. The increase in leasing transactions in Russia entails an increase in demand for insurance of such transactions, so the leasing object insurance is carried out in almost every transaction. At the same time, financial risks are not covered by insurance, despite the demand from lessors. One of the barriers to the spread of leasing financial risks insurance in project financing is credit organizations, which establish strict control over this process, depriving lessors and lessees of choice. Recommendations for credit organizations to reduce their influence on the leasing process in order to accumulate experience of financial risks insurance by insurance companies have been offered. The study of the issue will allow this type of investment activity to become more attractive for all participants of the transaction, and the step-by-step solution of the issues related to banking regulation of the leasing process will contribute to experience accumulation in such risks insurance.